Supramolecular dehydropeptide hydrogels: synthesis, properties and biomedical applications - Ferreira, Paula M. T. (2019)
Self-assembled low molecular weight peptide hydrogels have emerged in recent years as the new paradigm in biomaterials research due to their high water content; fully organic struc-ture; intrinsic nontoxicity and biocompatibility and fibrillar nanostructure indicative of the ex-tracellular matrix.1 The properties of peptide hydrogels can be tuned by design and there is a large variety of possible hydrogelator structures using proteinogenic and non proteinogenic aminoacids. Our research group has recently described a series of self-assembled hydrogels based on dehydrodipeptides N-protected with an aromatic moiety. The C-terminal dehy-droaminoacid residue (dehydrophenylalanine, dehydroaminobutyric acid and dehydroalanine) is prone to make the peptide resistant to prote-olysis and restrains the conformational freedom of the peptide.2 In this work the preparation and characterization of the new hydrogelators as well as the corresponding hydrogels will be presented together with some biomedical appli-cations of the new biomaterials prepared name-ly as drug delivery systems or as plataforms for theragnostics.